Exploring the genre of undergraduate teacher education acknowledgments - Porras, Anthony (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2019)
Genre-based studies in various disciplines have continuously flourished throughout the years. Despite this proliferation, local studies dealing with the acknowledgment section of the undergraduate theses tend to be premature most specifically in the field of Teacher Education (TE). The study aimed to analyze, through the presence of moves, the overall structure of the thirty (30) randomly sampled undergraduate acknowledgments from the field of TE using Hyland’s model. The findings revealed that the undergraduate acknowledgment structure was comprised of Thanking Move which is the most pervasive move, followed by the Reflecting Move. Though the Announcing Move was notpresent, one unique move, which is Thanking God, appeared to be dominating in the corpus. It is suggested for future studies to increase the number of the corpus in order to yield more interesting results and explore the socio-cultural aspect of the investigated genre.